Description of Heterorhabditis americana n. sp. (Rhabditida, Heterorhabditidae), a new entomopathogenic nematode species isolated in North America - Ricardo A. R. Machado; Joaquín Abolafia; María-Cristina Robles; Alba N. Ruiz-Cuenca; Aashaq Hussain Bhat; Ebrahim Shokoohi; Vladimír Půža; Xi Zhang; Matthias Erb; Christelle A. M. Robert; Bruce Hibbard (Parasites & Vectors)
Abstract Background Heterorhabditis are important biological control agents in agriculture. Two Heterorhabditis populations, S8 and S10, were isolated from agricultural soils in the United States of America. Molecular analyses, based on mitochondrial and nuclear genes, showed that these populations are conspecific and represent a novel species of the “Bacteriophora” clade. This species was named Heterorhabditis americana n. sp. and is described in this study. Methods To describe H. americana n. sp., we carried out phylogenetic reconstructions using multiple genes, characterized their morphology, conducted self-crossing and cross-hybridization experiments, and isolated and identified their symbiotic bacteria. Results Heterorhabditis americana n. sp. is molecularly and morphologically similar to H. georgiana. Morphological differences between the males of H. americana n. sp. and H. georgiana include variations in the excretory pore position, the gubernaculum size, the gubernaculum-to-spicule length ratio, the tail length, and the body diameter. Infective juveniles (IJs) of H. americana n. sp. differ from H. georgiana IJs because H. americana n. sp. IJs have an invisible bacterial cell pouch posterior to the cardia and a small posterior phasmid, whereas H. georgiana IJs have a visible bacterial cell pouch and an inconspicuous phasmid. Hermaphrodites of H. americana n. sp. and H. georgiana are differentiated by the body length, the nerve ring distance from the anterior end, the excretory pore distance from the anterior end, the anal body diameter, and the c′ ratio. Females of H. americana n. sp. can be differentiated from H. georgiana females by the anal body diameter and the c′ ratio. Reproductive isolation was confirmed, as H. americana n. sp. does not produce viable offspring with any of the species of the “Bacteriophora” clade. Heterorhabditis americana n. sp. is associated with the symbiotic bacterium Photorhabdus kleinii. Conclusions Based on the observed morphological and morphometric differences, the distinct phylogenetic placement, and the reproductive isolation, the nematode isolates S8 and S10 represent a novel species, which we named Heterorhabditis americana n. sp. This study provides a detailed characterization of this novel species, contributing to enhancing our knowledge of species diversity and evolutionary relationships of the Heterorhabditis genus. Graphical Abstract